Bentuk-Bentuk Pelanggaran Lalu Lintas Dan Upaya Penanggulangannya Oleh Kepolisian (Studi Kasus Di Polres Sragen) - Prihatini, Sri, Hartanto, S.H., M.Hum, Bambang Sukoco S.H.,M.H (2016)
This research aims to know the factors that cause society sragen disobeying traffic laws on the rule and the efforts that have been undertaken by parties to polres sragen in order to cope with traffic violations in order not to always increase year. The method of the approach used in this study are normative juridical approach methods, whereas this type of research is diskriptif, with the purpose of to provide meticulous data may be systematically and thoroughly about the description of the process of settlement of the law in traffic violations, as well as the prevention efforts by police. Using this type of primary data and secondary data. Method of data collection in this research study by means of interviews and the study of librarianship. Analysis on the use the author in this study is the analysis of qualitative data. Based on the results of the research and the discussion then it can be inferred that the constraints that cause society not conformed to the rule of law in the area of traffic areas in Sragen, contributes to the community by the drivers of vehicles and enforcement law i.e. the police. Violations of traffic related human factor was the lack of attention from the public to abide by traffic regulations, while from the police is the assertiveness of police in erecting a traffic violation that occurred. Efforts made by the police in tackling traffic offences in Sragen district, namely through the efforts of preventive (precautionary) and installation of traffic signs along the way as a guide for users of the road, as well as conducting patrols regularly. While the repressive is coaching done the police when making the offence.